The role of counselor in preventing students’ attitudes toward cheating - Meilinda Meilinda; Mudjiran Mudjiran; Sufyarma Marsidin (International Conferences on Educational, Social Sciences and Technology)
Attitude toward cheating is formed based on someone’s perspective, belief, and knowledge or information received about cheating. If the students’ attitude toward cheating ispositive, their affective evaluation tends to accept and assume that cheating is normal. The positive attitudes are more likely to be an action of approaching, liking even expecting cheating behavior to occur. Conversely, if the students’ attitude is negative, their affective evaluation tends to reject, disagree, and assume that cheating is a prohibited act and leadstheir attitude to become negative behavior. Therefore, counselors need to provide the understanding of guidance and counseling service as one of alternatives in preventing students’ cheating. This paper discusses the concept of cheating and the role of counselor to help students avoid cheating.